Cross-border DCF valuation: discounting cash flows in foreign currency - Andreas Schüler (Journal of Business Economics, 2020)
The paper seeks to develop a comprehensive framework to cross-border discounted cash flow valuation. Although the literature on company valuation and on international financial management is vast, such a framework has not yet been proposed. We build upon well-known fundamentals and relevant contributions, e.g. on the derivation of the risk-adjusted rate of return. Relevant risks are exchange rate risk, business risk, financial risk, the risk of the tax effects induced by debt financing, and the risk of default. Additional tax effects beyond the well-known tax shield on interest expenses must be considered. Risk discounts from cash flows and risk premia to be added to risk-free interest rates are derived according to the global capital asset pricing model. A conceptual choice occurs not only between the foreign currency and the home currency approach, but also regarding the estimation of future exchange rates. The paper shows how a valuation can be implemented with or without consideration of covariances between cash flows and rate of returns with exchange rates. It also derives the discount rates if forward exchange rates are applied. We discuss the consequences of assuming the uncovered interest parity to hold. We assume deterministic debt and apply the adjusted present value approach. In addition, we derive the RADR to be used in the flow to equity and weighted average cost of capital approach. The paper addresses not only the valuation of a foreign company, but also the valuation of a domestic company that generates cash flows in foreign currency and/or uses debt in foreign currency.
Keywords: G15; G32; M16; 650; Exchange risk; Foreign currency; Cross-border valuation; Valuation; International finance